2019
DOI: 10.3389/fenrg.2019.00009
|View full text |Cite
|
Sign up to set email alerts
|

Coconut Fiber Cement Panels as Wall Insulation and Structural Diaphragm

Abstract: This study considers the applications of natural fiber composites in affordable housing projects located in the two districts of Gujarat, India, and Gorkha, Nepal, with the goal of addressing issues of thermal comfort and lateral loading from seismic activity. To help alleviate some of these issues, the team worked with the Hunnarshala Foundation, in Bhuj, India, to develop a fiber cement composite that could be applied to the interior or exterior of a home and provide both insulative and structural improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Biocomposite thermal conductivity testing using a testing device in the form of a guarded hot-plates system is operated by referring to ASTM C177-04 [ 11 ]. Thermal conductivity is calculated as follows: …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biocomposite thermal conductivity testing using a testing device in the form of a guarded hot-plates system is operated by referring to ASTM C177-04 [ 11 ]. Thermal conductivity is calculated as follows: …”
Section: Resultsmentioning
confidence: 99%
“…The use of coconut fiber thermal panels as wall insulation in people's homes in Nepal provides energy savings due to the reduction in carbon emissions resulting from burning wood in the house for heating. Energy savings during winter in Bhuj are around 6%–11% in a year which is equivalent to 964 kwh [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sustainable biopolymer composites have been researched with the use of organic fibers like coir [6,7]. A coir-cement composite used as an insulator was found to reduce thermal conductivity by 0.16-0.19 W/mK [8]. Further, induced ventilation techniques including solar chimney and air vents are beneficial to exhaust hot air from the building at a quick rate.…”
Section: Introductionmentioning
confidence: 99%
“…They revealed that natural fibre had an eligible mechanical property as that of reinforcement materials. In recent years, there have been some research studies on applications of coconut and palm oil fibres such as wall panelling systems [13], wall insulation [14], cement boards partition [15], slabs [16], tiles bricks, internal and external wall, cabinet [17], hollow blocks [18], and wall coating for improving thermal properties [19]. However, no examples of the practical use of natural fibres in the construction industry and evidence that natural fibres have a high potential in terms of physical and mechanical properties are provided.…”
Section: Introductionmentioning
confidence: 99%